SOCIAL MEDIA, THE 21ST CENTURY TOOL AT THE SERVICE OF RECRUITING TALENT - SECARĂ CARMEN-GABRIELA; BRÎNZ EA VICTORIA-MIHAELA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
Social media changes the way in which companies interact in technology-mediated ways to most stakeholders and managers can not afford to ignore the new ways in which interactions with customers, employees, shareholders and many other important components occur as a result of the widespread availability broad and creative use of these new technologies. Social media seems to offer attractive and valuable opportunities to attract and hire talented individuals, supporting the quality, quantity and fairness of labor relations. This paper aims to show how social media can better support recruitment activities taking into account, in particular, the needs and expectations of young workers and talented professionals in a more general context.